150 YEARS OF THE OIL PRICE–MACROECONOMY RELATIONSHIP. (28th June 2017) - Serletis, Apostolos; Mehmandosti, Elaheh Asadi
Abstract : We use the longest span data that have ever been studied before (from 1870 to 2014) to investigate the relationship between the price of oil and the level of economic activity in the United States. In the context of a bivariate (identified) structural generalized autoregressive conditional heteroscedasticity (GARCH)-in-Mean VAR in real output growth and the change in the real price of oil, we find that uncertainty about oil prices has had a negative and significant effect on real output. We also find that the responses of real output growth to positive and negative shocks are not very informative of whether they are symmetric or asymmetric, and that accounting for oil price uncertainty tends to amplify the negative dynamic response of real output growth to unfavorable (positive) oil price shocks.